Measuring systematic risk from managerial organization capital - Yildirim, Alev; Allen, Linda (Journal of Business Finance & Accounting, 2021)
3 citations (Crossref) [2023-10-31]
Keywords: dept.fin; peer-reviewed

A coronavirus outbreak and sector stock returns: a tale from the first ten weeks of 2020 - Nguyen, Khoa Huu (Applied Economics Letters, 2021)
This paper examines early impacts of the COVID-19 outbreak on stock returns of 11 sectors using the firm-level stock price data from 10 countries. Results show that investors across sectors and countries respond differently during the outbreak. Communication Services, Consumer Staples, Health Care, Information Technology, and Utilities sectors consistently perform relatively well, compared to other sectors, in all countries except Italy, Japan and U.S. Conversely, Energy sector suffers greatest abnormal negative returns, among all sectors, in countries including Canada, Italy, U.K. and U.S. Furthermore, Japan and U.S. have highest numbers of abnormally and negatively affected sectors. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
4 citations (Crossref) [2023-10-31] https://search.bvsalud.org/global-literature-on-novel-coronavirus-2019-ncov/resource/en/covidwho-1347348
Keywords: dept.fin; peer-reviewed

Economic forecasts, anchoring bias, and stock returns - Birz, Gene; Dutta, Sandip; Yu, Han (Financial Management, 2021)
By utilizing survey forecasts of macroeconomic statistics, we find that market participants’ expectations are not rational as they exhibit an anchoring bias. The forecasts systematically underpredict macroeconomic statistics and the forecast errors are predicted by past macroeconomic announcements. Most importantly, we find that the stock market does not see through this bias, that is, we find statistically significant stock price effects of “anticipated” components of macroeconomic announcements. Investors overweight the importance of historical information and do not make sufficient adjustments after the arrival of new information. © 2021 Financial Management Association International
6 citations (Crossref) [2023-10-31]
Keywords: dept.fin; peer-reviewed

Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85096023364
Keywords: dept.eco; dept.fin; peer-reviewed